Native trees of the Midwest : identification, wildlife values, and landscaping use - Weeks, Sally S., 1956- (Purdue University Press, 2010)
Designed to introduce the student, layperson and professional to the native trees of Indiana and surrounding states by providing hard-to-find color images and updated nomenclature from previous, state-specific field guides.